Characterization of 3,3′-iminodipropionitrile (IDPN) damaged utricle transcriptome in the adult mouse utricle - Mengyao Tian; Mengyao Tian; Jingyuan Huang; Jingyuan Huang; Hairong Xiao; Hairong Xiao; Pei Jiang; Pei Jiang; Xiangyu Ma; Xiangyu Ma; Yanqin Lin; Yanqin Lin; et al. (Frontiers in Molecular Neuroscience)
Utricle is an important vestibular sensory organ for maintaining balance. 3,3′-iminodipropionitrile (IDPN), a prototype nitrile toxin, has been reported to be neurotoxic and vestibulotoxic, and can be used to establish an in vivo damage model of vestibular dysfunction. However, the mechanism of utricular HCs damage caused by IDPN is unclear. Here, we first studied mice balance behavior and HCs damage in IDPN utricle damage model, and found that IDPN injection in vivo can cause vestibular dysfunction and HCs damage, which is more pronounced than neomycin damage model. Then we used RNA-seq to characterize the transcriptome of IDPN damaged utricle in detail to identify genes and pathways that play roles in this process. We found 1,165 upregulated genes and 1,043 downregulated genes in IDPN damaged utricles, and identified that NF-κB pathway and TNF pathway may play important roles in IDPN damage model. Our study provides details of transcriptome of IDPN utricle damage model for further study of vestibular dysfunction.